La seguridad y salud ocupacional y el bienestar laboral en la Cooperativa de Ahorro y Crédito Juan Pío de Mora Ltda., cantón San Miguel de la provincia Bolívar, año 2024 - Hurtado Yanza, Geomayra Pamela (2024)
The general objective of this research was to investigate occupational health and safety in word well-being in the Juan Pío de Mora Savings and Credit Cooperative Ltda., San Miguel canton Bolívar province, year 2024.The methodology used was explanatory, descriptive, field, non-experimental and transversal, with a quantitative approach. Data were collected through surveys and analyzed statiscally. The main results indicated that the most prevalent occupational diseases included eye problems and muscle pain (26.70%), stress and anxiety (33.30%) and respiratory problems (13.30%). In addition,27% of workers reported headaches frequent,20%presented irritability and 17% anxiety, highlighting the need to implement programs to reduce work stress. The conclusions reveal a significant correlation between the implementation of occupational health and safety measures and the increase in labor well- being in the cooperative. Areas for improvement in current occupational health and safety conditions were identified, suggesting the need to develop specific strategies. It is recommended to implement activities and polices that support the physical and mental well- being of all employees, improve word environment conditions and continue research on best practices in occupational health and safety and workplace well-being.